The protective effects of aqueous garlic extract against water avoidance stress-induced mast cell degranulation in the dermis - (:unkn) unknown (My University, 2005)
Objective: The aim of the present study was to investigate the effects of aqueaous garlic extract (AGE) on water avoidance stress (WAS)-induced degranulation of mast cells in the dermis. Material and Methods: Wistar albino rats were exposed to WAS (WAS group). After exposing the animals to WAS (WAS plus AGE group), 250mg/kg AGE was injected i.p.. Dermal mast cells were stained with toluidine blue and investigated using light microscopy. Results: The number of both granulated and degranulated mast cells was higher in the WAS group, when compared to the control group. The number of mature granulated and degranulated mast cells was lower in the WAS plus AGE group when compared to the WAS group. Conclusion: Chronic AGE treatment reduced WAS-induced infiltration and activation of mast cells in the dermis and may provide a useful therapeutic option in stress-induced skin disorders.
Keywords: Aqueaus garlic extract; Dermis; Mast cell; Water avoidence stress